2002
DOI: 10.2135/cropsci2002.1291
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Polymorphism as Detected by C‐Banding Patterns in Chilean Alfalfa Germplasm 1

Abstract: A cytogenetic investigation was conducted on the tetraploid alfalfa [Medicago sativa subsp. sativa (L.) L. & L.] Chilean germplasm source PI 536534 using the combined techniques of C‐banding and image analysis. Cluster and multiple correspondence analyses were utilized to compare the C‐banding patterns of the Chilean germplasm source and the previously published African germplasm source. Cytogenetic analyses revealed polymorphisms for heterochromatic DNA in the 19 plants observed in detail. Abundant variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This trend can also be observed among the four coffee species studied. C-banding is considered a useful technique for demonstrating heterochromatin in chromosomes (Hoshi et al 1998) and a reliable chromosome marker, along with karyomorphometric data in comparative studies, allowing for improved characterization of species, populations and germplasms (Bauchan et al 2002;Dong et al 2011). Despite the small size of coffee chromosomes, it was possible to obtain C-bands.…”
Section: Discussionmentioning
confidence: 99%
“…This trend can also be observed among the four coffee species studied. C-banding is considered a useful technique for demonstrating heterochromatin in chromosomes (Hoshi et al 1998) and a reliable chromosome marker, along with karyomorphometric data in comparative studies, allowing for improved characterization of species, populations and germplasms (Bauchan et al 2002;Dong et al 2011). Despite the small size of coffee chromosomes, it was possible to obtain C-bands.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies in Medicago have reported useful data to i) identify parental chromosomes in hybrids (Bauchan and Hossain 1997); ii) to discriminate germplasm sources from cultivated species (Bauchan et al 2002); and iii) to contribute towards the integration of molecular, genetic and cytogenetic maps (Kulikova et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several cytogenetic studies have been conducted to karyotype the somatic chromosomes of tetraploid alfalfa (Agarwal and Gupta, 1983; Falistocco, 1987; Schlarbaum et al, 1988; Falistocco et al, 1995; Bauchan and Hossain, 2001a,b; Bauchan et al, 2002). The alfalfa karyotype consists of one set of homologous chromosomes with a satellite (chromosome 8), four sets of submetacentric chromosomes (chromosome 1–4) and three sets of metacentric chromosomes (chromosomes 5–7).…”
mentioning
confidence: 99%
“…The alfalfa karyotype consists of one set of homologous chromosomes with a satellite (chromosome 8), four sets of submetacentric chromosomes (chromosome 1–4) and three sets of metacentric chromosomes (chromosomes 5–7). Chromosome banding studies have identified individual chromosomes of M. sativa subspecies, including coerulea, falcata (Bauchan and Hossain, 1997, 1998a, 1999a,b,c) and sativa (Falistocco et al, 1995; Bauchan and Hossain, 2001a,b; Bauchan et al, 2002). Bauchan and Hossain (2001b) evaluated the African tetraploid population and concluded it resembled the C‐banding pattern of diploid M. sativa subsp.…”
mentioning
confidence: 99%
See 1 more Smart Citation